Peningkatan Perencanaan Karier Melalui Layanan Informasi Konsep Ikigai Pada Siswa Kelas XI di SMAIT Nurul Ilmi Kota Jambi - Rizqullah, Dhilal; Rasimin, Rasimin; Sarman, Freddi (Universitas Mathla'ul Anwar Banten, 2024)
Improving Career Planning Through Ikigai Concept Information Services for XI Students Class at SMAIT Nurul Ilmi Jambi City. Students have their own challenges during the process of determining their choice of major for further education. The core problem felt by students is that students do not know themselves, their potential, as well as their interests and talents. This condition become worse by the lack of guidance received, students are less likely to search for information about new and existing majors, do not carry out career planning, and not aware of the latest developments related to job prospects. If this problem is not addressed, it can have a negative impact on a student in the future, this is because career planning before making a career choice is very important and crucial. Ikigai is a life concept that leads individuals to formulate their life goals by discovering the four concepts that form ikigai consisting of passion, mission, profession and vocation. This research is a quasi-experimental quantitative research using a pre-test and post-test with non-equivalent control group design. The subjects in this study were 56 student from XI class. Therefore, the career choices taken should be in accordance with one's own desires and based on careful career planning. This research aims to determine the level of students' career planning before and after being given treatment in the form of ikigai concept information.